Case Report: Imaging Features and Successful Management of Ureteral Stenosis in a Kitten With Bilateral Atypical Papillary Transitional Mucosal Hyperplasia - Kwon, Minji; Kim, Sungsoo; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2022)
A 3-month-old cat weighing 2.62 kg was brought to the VIP Animal Medical Center with vomiting, diarrhea, anorexia, and depression. Laboratory findings confirmed azotemia with elevated blood urea nitrogen (BUN) (168.9 mg/dl) and creatinine (5.9 mg/dl) and symmetric dimethylarginine (SDMA) (86 μg/dl). Abdominal radiography revealed bilateral renomegaly. Ultrasonography revealed bilateral hydronephrosis and left partial and right complete ureteral obstructions with bilateral focal irregular and circumferential thickenings at ureters. Reduction of bilateral renal function was confirmed through excretory urography on computed tomography. The cat underwent subcutaneous ureteral bypass surgery on the left kidney, right nephrectomy, and bilateral ureterectomy. Histopathology of bilateral ureteral irregular and circumferential thickening revealed bilateral atypical papillary transitional mucosal hyperplasia. Three days after surgery, the left hydronephrosis resolved, and azotemia was almost resolved. This is the first report of successful management of ureteral stenosis with congenital papillary transitional mucosal hyperplasia in a kitten using multimodality imaging.